City Branding Kota Ternate: Branding of Ternate City - Johan Fahri; Fichriyanto M Ahmad (Society, 2021)
City branding has become a massive effort by many cities as tourist destinations to promote the city nationally and internationally. Ambon City, the Capital of Maluku Province, known as the “City of Music,” and the City of Solo with “Solo the Spirit of Java,” are examples of city branding. In North Maluku Province, Ternate City has a long history of colonialism, international trade, and a developing city. Unfortunately, inconsistencies still exist in how the city should be known. This study aims to identify and define city branding by using the constructivist grounded theory method. The themes identified were quality tourism, economic value, community engagement, stakeholder consensus, legendary ancient leadership, and historic and renowned commodity. Six main themes are theoretically based on how to branding Ternate city and involving seven important participants. These themes are then used to define the branding of Ternate City. Current research offers a testable model to brand a place or city based on the identified subjects. At the same time, potential future studies are also suggested regarding the weaknesses of the current study.